Kontribusi Sekolah Damai Sebagai Wujud Pelaksanaan Moderasi Beragama - Moch. Tolchah; Kasim Yahiji; Said Subhan Posangi; Nur Ainiyah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This article focuses on the contribution of the peace school program as one of the implementations of religious moderation strategies in schools. This qualitative research with a phenomenological approach was applied using structured interviews and documentation studies at SMUN Sugihwaras Bojonegoro as a pilot school for the peace school program. The empirical data illustrates the concept of the peace school program, the implementation of the peace school program, and the contribution of the peace school program as a strategy for implementing religious moderation in schools. This study found that the peace school program is one of the programs that significantly contributes to realizing the implementation of religious moderation in schools. This program implements the concept of religious moderation that focuses on inculcating and internalizing the values ​​of tolerance and peace. This program targets the three main pillars of the education process: policies, practices of tolerance and peace in the school environment, and the management of student organizations.